Determinants of Barter in Russia : An Empirical Analysis - Mumssen, Christian (IMF Working Papers; Working Paper ;, 2000)
This paper analyzes the causes and consequences of non-monetary transactions in Russia, drawing on a large enterprise survey. We show that barter and offsets are linked to liquidity problems at the level of the firm and to arrears in particular. We find evidence that the state has channeled implicit subsidies to enterprises in the form of tax and utility offsets. The findings help explain the rise of non-monetary transactions during much of the 1990s. We show that non-monetary transactions inhibit enterprise restructuring. Our findings suggest that a policy solution to the non-cash problem would require the state and public utilities to phase out arrears and offsets.